Hubungan Pemberian Coklat Hitam Dengan Derajat Dismenore Pada Mahasiswi Kedokteran Universitas Andalas - Desti Angraini; Asterina Asterina; Andri Friadi (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: Dark chocolate is a variant of chocolate that contain more cocoa(50%-85%) and a big concenteration of flavonoid that act as an inhibitor to some enzyme and increase antioxidant protection which could affect the level of dysmenorrhea. Objective: This study was conducted to determine the relationship between administrations of dark chocolate and dysmenorrhea level on medical student batch 2017 of Andalas University. Method: The type of research is true experiment pretest-posttest with control group that conducted in medical faculty of Andalas University with a sample size of 32. The instruments of this study were questionniare. Data was analyzed using the dependent and independent T-test.Results: The results showed that the majority of student with dysmenorrhea experiencing pain at the number 8 (28,1%) of visual analog scale. Bivariate analysis showed the value of p = 0.000 (p <0.05) where there was a significant relationship between administrations of dark chocolate with dysmenorrhea level and p=0,920 (p<0,05) where there is no significant difference between administration of 70% and 54% dark chocolate on medical student batch 2017 of Andalas University. Conclusion: There was a relationship between administrations of dark chocolate with dysmenorrhea level but, no significant difference between administration of 70% and 54% dark chocolate